MINDFULNESS BASED COGNITIVE THERAPY UNTUK MENURUNKAN TINGKAT DEPRESI PADA ORANG DENGAN HIV - Atmadja, Kessy; Edwina, O. Irene Prameswari; Victoriana, Evany (Universitas Islam Indonesia, 2025)
ABSTRACT: Depression is a common disorder experienced by people living with HIV (PLHIV), negatively affecting their quality of life and treatment adherence. Mindfulness-Based Cognitive Therapy (MBCT) has been developed to help individuals cope with depression by enhancing awareness and acceptance of present experiences. This study aimed to evaluate the effectiveness of MBCT in reducing depression levels among PLHIV. A total of eight participants who met the inclusion criteria were recruited from a local HIV community. This study used an experimental pretest–posttest design, with the Beck Depression Inventory II (BDI-II) and the Five Facet Mindfulness Questionnaire (FFMQ) as measurement tools. The intervention consisted of eight group-based sessions of MBCT. The results showed that MBCT significantly reduced depression levels in PLHIV after the intervention compared to before, indicating that MBCT is an effective approach to mitigating depressive symptoms. These findings suggest that MBCT can serve as a practical psychological intervention to improve emotional well-being and treatment adherence in PLHIV, as well as contribute theoretically to the growing evidence on mindfulness-based approaches for chronic illness populations. Key words: Depression, mindfulness-based cognitive therapy, people living with HIV. ABSTRAK: Depresi merupakan gangguan umum yang dialami orang dengan HIV (ODHIV), yang berdampak negatif terhadap kualitas hidup serta ketaatan terhadap pengobatan. Terapi Kognitif Berbasis Mindfulness (MBCT) dikembangkan untuk membantu individu mengatasi depresi dengan meningkatkan kesadaran dan penerimaan terhadap pengalaman saat ini. Penelitian ini bertujuan untuk mengevaluasi efektivitas MBCT dalam menurunkan tingkat depresi pada ODHIV. Sebanyak delapan partisipan yang memenuhi kriteria inklusi direkrut dari salah satu komunitas HIV. Penelitian ini menggunakan desain eksperimen prates-pascates, dengan Beck Depression Inventory II (BDI-II) dan Five Facet Mindfulness Questionnaire (FFMQ) sebagai alat ukur. Intervensi dilakukan melalui delapan sesi kelompok MBCT. Hasil penelitian menunjukkan bahwa MBCT secara signifikan menurunkan tingkat depresi pada ODHIV setelah intervensi dibandingkan dengan sebelum intervensi. Temuan ini menunjukkan bahwa MBCT dapat menjadi intervensi psikologis yang efektif untuk meningkatkan kesejahteraan emosional dan kepatuhan pengobatan pada ODHIV, serta memberikan kontribusi teoretis terhadap pengembangan pendekatan berbasis mindfulness pada populasi dengan penyakit kronis. Kata kunci: Depresi, mindfulness-based cognitive therapy, Orang dengan HIV.